Lead-free organic–inorganic tin halide perovskites for photovoltaic applications - Noel, N; Stranks, S; Abate, A; Wehrenfennig, C; Guarnera, S; Haghighirad, A; Sadhanala, A; Eperon, G; Pathak, S; Johnston, M; Petrozza, A; Herz, L; et al. (Royal Society of Chemistry, 2014)
Already exhibiting solar to electrical power conversion efficiencies of over 17%, organic-inorganic lead halide perovskite solar cells are one of the most promising emerging contenders in the drive to provide a cheap and clean source of energy. One concern however, is the potential toxicology issue of lead, a key component in the archetypical material. The most likely substitute is tin, which like lead, is also a group 14 metal. While organic-inorganic tin halide perovskites have shown good semiconducting behaviour, the instability of tin in its 2+ oxidation state has thus far proved to be an overwhelming challenge. Here, we report the first completely lead-free, CH3NH 3SnI3 perovskite solar cell processed on a mesoporous TiO2 scaffold, reaching efficiencies of over 6% under 1 sun illumination. Remarkably, we achieve open circuit voltages over 0.88 V from a material which has a 1.23 eV band gap.